2019
DOI: 10.3844/jcssp.2019.594.611
|View full text |Cite
|
Sign up to set email alerts
|

Metaheuristic Algorithms for Independent Task Scheduling in Symmetric and Asymmetric Cloud Computing Environment

Abstract: Cloud Computing (CC) is a recent technology in the Information and Communication Technology (ICT) field. It provides an on-demand access to the shared pool of resources via virtualization. Large enterprises move toward CC due to its flexibility and scalability driven from its elastic pay-per-use model. To provide ensured efficient performance to users, tasks should be efficiently mapped to available resources. Therefore, Task Scheduling (TS) is significant issue in the CC technology. TS is a NP-complete optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Metaheuristics techniques are based on analogues of biological concepts. It has been demonstrated that metaheuristic-based strategies can achieve near-optimal solutions in a reasonable amount of time for some complex problems [2,28]. Metaheuristic approaches were used to address resource scheduling difficulties such as makespan and response time reduction.…”
Section: Metaheuristic Techniques Used In Cloud Task Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Metaheuristics techniques are based on analogues of biological concepts. It has been demonstrated that metaheuristic-based strategies can achieve near-optimal solutions in a reasonable amount of time for some complex problems [2,28]. Metaheuristic approaches were used to address resource scheduling difficulties such as makespan and response time reduction.…”
Section: Metaheuristic Techniques Used In Cloud Task Schedulingmentioning
confidence: 99%
“…Cloud computing is a modern computing model that offers virtualization computing services as a utility to Cloud service users [1][2][3][4]. It is a concept for obtaining resources from a customizable shared resource, such as a group of networks, servers, storage, utilities, and applications, in instantaneously and based on request.…”
Section: Introductionmentioning
confidence: 99%
“…Cloud computing is a modern computing model that offers the virtualization of computing services as a utility to Cloud service users [1][2][3][4]. It is a concept for obtaining resources from a customizable shared resource, such as a group of networks, servers, storage, utilities, and applications, instantaneously and based on request.…”
Section: Introductionmentioning
confidence: 99%
“…Heuristic and metaheuristic scheduling techniques have been used to address the task scheduling problem in cloud computing [2,16]. For more trivial concerns, heuristic methods provide optimal results, but, as the size of the problem rises, the solutions generated by these algorithms will be less optimal.…”
Section: Introductionmentioning
confidence: 99%
“…Several metaheuristic algorithms that mimic the actions of insect or animal classes in nature have been developed using a combination of deterministic rules and randomness [9] [11]. Many of the optimization problems that can be formulated are extremely nonlinear, with multimodal objective landscapes and a series of dynamic, nonlinear constraints [12][13] [14].…”
Section: Introductionmentioning
confidence: 99%